Study of bryophytes of the Bosque Sagrado da Guarita, Bom Princípio of Piauí, Piauí, Brazil (Research, Society and Development, 2021)
The present work refers to the study of the bryoflora occurring in Guarita Sacred Forest, Bom Princípio do Piauí, where the bryophyte flora, in terms of taxonomic identification criteria, was previously unknown. For this study, eight collections were carried out in 2016, five of which were concentrated in the rainy season (February-April) and three in the dry season (July-September). 51 specimens were collected and 12 species of bryophytes were identified, among which two are hepatic: Riccia brasiliensis and R. fruchartii and 10 mosses: Archidium ohiense, Calymperes palisotii, Entodontopsis leucostega, Fissidens amoenus, F. angustifolius, F. guianensis var. guianensis, F. zollingeri, Hyophiladelphus agrarius, Hyophila involuta and Octoblepharum albidum. Among the six families in the area, Fissidentaceae was more representative, with four species. There was predominance of the rock substrate. Identification keys, descriptions, illustrations and geographic distribution data are being provided. This study contributes to the dissemination of bryophytes to Brazil, as well to bring three new citations to the bryophylla of Piauí.